The effect of alpha-melanocyte stimulating hormone on gentamicin-induced acute nephrotoxicity in rats - (:unkn) unknown (JOHN WILEY & SONS LTD, 2007)
The effect of a-melanocyte stimulating hormone (alpha-MSH) was investigated on gentamicin-induced acute renal injury in rats. Sprague-Dawley rats (200-250 g; n = 8-10) were treated with gentamicin sulphate (GEN; 80 mg kg(-1)) or saline intraperitoneally for 7 consecutive days. alpha-MSH was administered at a dose of 25 mu g rat(-1) day(-1) following GEN or saline injections. On day 8, all animals were decapitated. Trunk blood and 24 h urine were collected to measure the serum creatinine levels, blood urea nitrogen (BUN) levels and to calculate the creatinine clearance values. The kidneys were excised for histological evaluation and for the measurement of malondialclehyde (MDA) levels, glutathione (GSH) contents and myeloperoxiclase (MPO) activity. Treatment with a-MSH reduced the severity of the renal lesions microscopically, decreased MDA content and MPO activity and restored GSH in kidney samples. However, it did not restore the impaired renal function tests due to GEN challenge. In conclusion, a-MSH treatment has a beneficial effect on GEN-induced acute nephrotoxicity, as confirmed by histological evaluation and biochemical assays; but it does not improve GEN-induced renal dysfunction. The mechanism of the protective effect could be attributed, at least in part, to decreased tissue leukocyte infiltration and thus, to decreased oxygen-derived reactive metabolite production. Copyright (c) 2007 John Wiley & Sons, Ltd.
Keywords: gentamicin; alpha-melanocyte stimulating hormone; nephrotoxicity; renal injury; rat; ACUTE-RENAL-FAILURE; NF-KAPPA-B; LIPID-PEROXIDATION; INFLAMMATION; INJURY; MSH; NEPHROPATHY; NEUTROPHILS; INHIBITION; MODULATION